A Critical Recognition of the A Philosophy of War from Moseley’s View - Mohammad Reza Ahmadi Tabatabai (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Addressing the issue of the philosophy of war difficult. In other words, the relationship between Philosophy and war seems to be a difficult one. Alexander Moseley is a Political Philosophy Editor for the IEP (Internet Encyclopedia of Philosophy and he has lectured on the Philosophy and morality of war at several British universities. In his book called The Philosophy of War, he explained why humans fight against each other? He said, what I hope to establish in this work is that the Principles of war’s origins involve all aspects of our nature, culture, and thinking. We fight because we believe in fighting, and our beliefs have to change if we wish to abandon war. The research method in this book and this article is analytical and philosophical. The main question in “The Philosophy of War” is why humans fight and how through changing their beliefs and attitudes toward this devastating and ominous event, they can stand against humans and governments.